PENGARUH ORIENTASI PASAR, INOVASI PRODUK, DAN ORIENTASI KEWIRAUSAHAAN DALAM MENINGKATKAN KINERJA PEMASARAN UMKM KULINER KECAMATAN JAGAKARSA - Ega Oktavia (2022)
This research is a quantitative research that aims to determine the effect of market orientation, product innovation, and entrepreneurial orientation in improving the marketing performance of culinary SMEs in Jagakarsa District. The population in this study were culinary SMEs in the Jagakarsa District, South Jakarta. Then the number of samples determined by the Slovin formula was 94 respondents and the data was collected through a questionnaire using the google form. Using descriptive analysis techniques and inferential analysis through the SmartPLS 3.0 software test tool. while the hypothesis test is statistical t test. The results obtained from this study are (1) market orientation has a significant effect in improving marketing performance with a coefficient value of 0.436; (2) product innovation has a significant effect on improving marketing performance with a coefficient value of 0.179; (3) entrepreneurial orientation has a significant effect on improving marketing performance with a coefficient value of 0.391. With an R Square value of 0.972 or 97.2%.